Perspectives of guardians/parents in Portugal: interpreting the inclusive education policy through lived school practices - Carvalho, Ana Eloisa; Veiga, Amélia (Frontiers in Education, 2025)
IntroductionIn Portugal, the Legal Framework for Inclusive Education (Decree-Law 54/2018) replaced the Legal Framework for Special Education (Decree-Law 3/2008), which applied exclusively to students with permanent difficulties in accessing the curriculum. The new framework introduced changes to school organization aimed at addressing the diversity of needs of all students. These changes align with the personalization of the educational process, particularly through the multi-level approach (MLA) to the curriculum and the increased involvement of the educational community, where the role of the guardian becomes increasingly central. The impact of these changes remains insufficiently particularly from the perspectives of guardians/parents.MethodsThe article analyses how the changes mentioned are interpreted and translated in practice, following the theoretical-methodological proposal of Stephen Ball’s policy cycle and the thematic analysis method. Semi-structured interviews were conducted with eight guardians of students whose school trajectories are currently shaped by selective (MS) and/or additional (MA) measures within the MLA established by Decree-Law 54/2018, and which had previously been shaped by the support framework provided by Decree-Law 3/2008. Participants were drawn from four school clusters located in different regions of mainland Portugal (Centro; Lisboa e Vale do Tejo; Alentejo; Algarve), ensuring a degree of geographical diversity in the data collection process.ResultsThe results indicate progress compared to the previous policy repealed by Decree-Law 54/2018, particularly in the identification of educational measures better aligned with students‘ needs and in the development of more collaborative decision-making processes between schools and the families. However, the translation of these advances into effective learning opportunities both in terms of quality and equity has been constrained or hindered by structural challenges, namely the lack of adequate human resources and the limited autonomy of schools.DiscussionThis study highlights how inclusive education policy evolves through the interaction of various contexts within the policy cycle, emphasizing the role of institutional actors in the context of practice, who interpret, translate and enact the policy in diverse ways. At the same time, it reveals that a lack of resources and limited school autonomy serve as significant barriers to fostering more inclusive educational environments across the schools examined. These challenges, as pointed out by guardians/parents, highlight the need for greater investment and enhanced local autonomy if the changes introduced by the current Legal Framework for Inclusive Education are led to meaningful educational transformation that effectively address the diverse needs of all students.